Diffusion-weighted MRI and ADC versus FET-PET and GdT1w-MRI for gross tumor volume (GTV) delineation in re-irradiation of recurrent glioblastoma. (January 2019) - Popp, Ilinca; Bott, Stefan; Mix, Michael; Oehlke, Oliver; Schimek-Jasch, Tanja; Nieder, Carsten; Nestle, Ursula; Bock, Michael; Yuh, William T.C.; Meyer, Philipp Tobias; Weber, Wolfgang A.; Urbach, Horst; et al.
Highlights: 2/3 of ADClow areas are found outside MRI contrast enhancement and FET uptake areas. Restricted diffusion areas are only partially included in the re-irradiation volume. Recurrences co-localize better with baseline GdT1w-MRI and FET-PET/CT than with ADC. Abstract: Background and purpose: GTV definition for re-irradiation treatment planning in recurrent glioblastoma (rGBM) is usually based on contrast-enhanced MRI (GdT1w-MRI) and, for an increased specificity, on amino acid PET. Diffusion-weighted (DWI) MRI and ADC maps can reveal regions of high cellularity as surrogate for active tumor. The objective of this study was to compare the localization and quality of diffusion restriction foci (GTV-ADClow) with FET-PET (GTV-PET) and GdT1w-MRI (GTV-GdT1w-MRI). Material and methods: We prospectively evaluated 41 patients, who received a fractionated stereotactic re-irradiation for rGBM. GTV-PET was generated automatically (tumor-to-background ratio 1.7–1.8) and manually customized. GTV-ADClow was manually defined based on DWI data (3D diffusion gradients, b = 0, 1000 s/mm 2 ) and parametric ADC maps. The localization of recurrence was correlated with initial GdT1w-MRI and PET data. Results: In 30/41 patients, DWI-MRI showed areas with restricted diffusion (mean ADC-value 0.74 ± 0.22 mm 2 /s). 66% of GTVs-ADClow were located outside the GdT1w-MRI volume and 76% outside increased FET uptake regions. Furthermore, GTVs-ADClow were only partially included in the high dose volume and received in mean 82% of the reference dose. An adjusted volume including GdT1w-MRI, PET-positive and restricted diffusion areas would imply a GTV increase of 48%. GTV-PET and GdT1w-MRI correlated better with the localization of re-recurrence in comparison to GTV-ADClow. Conclusion: Unexpectedly, GTV-ADClow overlapped only partially with FET-PET and GdT1w-MRI in rGBM. Moreover, GTV-ADClow correlated poorly with later rGBM-recurrences. Seeing as a restricted diffusion is known to correlate with hypercellularity, this imaging discrepancy could only be further explained in histopathological studies.